Phase I study of pembrolizumab in combination with ibrutinib for the treatment of unresectable or metastatic melanoma - Yao, Yuan; Yan, Yiyi; Suman, Vera J.; Dietz, Allan B.; Erskine, Courtney L.; Dimou, Anastasios; Markovic, Svetomir N.; McWilliams, Robert R.; Montane, Heather N.; Block, Matthew S. (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have been transformative in the treatment of patients with metastatic melanoma, but primary and secondary resistance to ICI treatment is common. One key mechanism for ICI resistance is the skewing of the immune response from a cytotoxic (Th1) to a chronic inflammatory (Th2) profile. The small molecule ibrutinib is a dual-target agent that inhibits Bruton’s Tyrosine Kinase (BTK) and Interleukin-2-inducible T-cell Kinase (ITK), a key regulator of Th2 immunity. Therefore, combining ibrutinib and pembrolizumab could potentially induce an increase in Th1 immune polarity in melanoma patients. We hypothesize that the combination would be well-tolerated and might result in clinical benefit for patients with metastatic melanoma. The primary aim of this phase I study was to evaluate the safety, tolerability, and determine the maximum tolerated dose (MTD) of ibrutinib in combination with pembrolizumab in patients with metastatic melanoma.MethodsA 3 + 3 phase I clinical trial was conducted in patients with unresectable Stage III or metastatic melanoma (stage IV) not amenable to local therapy. Pembrolizumab (200 mg/kg every 3 weeks) was combined with ibrutinib, administered orally at the dose assigned at the time of registration (140 mg daily, 280 mg daily, and 420 mg daily). Patients were treated until disease progression, intolerability, or patient decision to discontinue. Blood samples were collected after each cycle of treatment for immunophenotyping and Th1/Th2 polarity assessment based on immune response markers.ResultsBetween January 31, 2017 and January 9, 2023, 17 patients were enrolled. The MTD of ibrutinib in combination with pembrolizumab was determined to be 420 mg daily. The adverse events leading to discontinuation included: grade 4 ALT and AST increase (1 pt, DL0); grade 4 ALT increase with grade 3 AST increase (1 pt, DL1); and grade 3 hyponatremia, hypoxia, and maculo-papular rash (1 pt, DL1). Three of the 16 patients treated had objective responses (2 partial responses, 1 complete response) lasting over 8 months. The median progression-free survival was 3 months, and median and overall survival was 1.8 years. The combination treatment did not result in consistent increase in Th1 immune polarity.ConclusionIn conclusion, the maximum tolerated dose of ibrutinib in combination with pembrolizumab in patients with advanced or metastatic melanoma was established at 420 mg by mouth once daily. The combination was well-tolerated but did not result in a consistent increase in Th1 immune polarity; further investigation is needed to assess the relative clinical efficacy of this approach. (Funded by Pharmacyclics; ClinicalTrials.gov number: NCT03021460)Clinical trial registrationwww.clinicaltrials.gov, identifier NCT03021460.